Manajemen Risiko pada Badan Amil Zakat Nasional (BAZNAS) - Nina Triyani; Irfan Syauqi Beik; Lukman M Baga (Department of Islamic Economics, IPB University, 2017)
Risk occurs at any organization or business activity. It also does not close the possiblility of risk occurs at amil institutions. Types of risk are likely to happen often at amil institutions, namely risk on zakat fund collection, risk on zakat fund management, and risk on zakat fund distribution. Basically, zakat distribution must comply with the 8 ashnaf as written in the QS. At-Taubah: 60. This research was conducted on BAZNAS. The aim of this research is to help amil institutions in managing the possibility of risk, analyze the factors that effect the risks, do the risks mapping on zakat fund collection, zakat fund management, and zakat fund distribution, and also make mitigation to minimize the occurrence of the risks. The data was collected by using the survey method in internal BAZNAS and using ERM method for analysis.